Constructing Film Emotions: The Theory of Constructed Emotion as a Biocultural Framework for Cognitive Film Theory. Issue 2 (1st June 2022) - Justus, Timothy
Abstract: In the classical view of emotion, the basic emotions (anger, disgust, fear, joy, sadness, and surprise) are assumed to be natural kinds that are perceiver-independent. Correspondingly, each is thought to possess a distinct neural and physiological signature, accompanied by an expression that is universally recognized despite differences in culture, era, and language. An alternative, the theory of constructed emotion, emphasizes that, while the underlying interoceptive sensations are biological, emotional concepts are learned, socially constructed categories, characterized by many-to-many relationships among diverse brain states, physiological signs, facial movements, and their emotional meanings. This biocultural view permits a greater degree of cultural-historical specificity when interpreting the emotions of others. In this article, I consider the implications of the theory of constructed emotion for cognitive film theory, especially regarding the interpretation of depicted facial expressions of emotion as one aspect of cinematic expression. Particular attention is given to recent work revisiting the Kuleshov effect, in which the meaning of a character's facial expression is thought to change in the context of a montage.